РЕБЯТА ПОМОГИТЕ РЕШИТЬ, СДАЧА ЗАВТРА, СУММА И ПРОИЗВЕДЕНИЕ КОРНЕЙ ТАМ!!!СПАСИБО ЗА РАНЕЕ!

1

Ответы и объяснения

2013-10-07T01:48:19+04:00
(x^2-2x)-3x^2+6x-4=0=>(x^2-2x)-3(x^2-2x)-4=0
замена x^2-2x =t
подставляем
t^2-3t-4=0 =>
t_{1,2}=\frac{3 \pm \sqrt{9+16}}{2}, t_1=4,t_2=-1
обратная замена
\left[\begin{array}{c}x^2-2x=4\\ x^2-2x=-1\end{array}\right.=>\left[\begin{array}{c}x_{3,4}=\frac{2 \pm2\sqrt5}{2}\\ x_{1,2}=-1\end{array}\right.
произведение корней
-1*(-1)*\frac{2+2\sqrt5}{2}*\frac{2-2\sqrt5}{2}=\frac{4-4*5}{4}=-4